FGF-2-Induced Human Amniotic Mesenchymal Stem Cells Seeded on a Human Acellular Amniotic Membrane Scaffold Accelerated Tendon-to-Bone Healing in a Rabbit Extra-Articular Model. (6th January 2020) - Zhang, Jun; Liu, Ziming; Li, Yuwan; You, Qi; Yang, Jibin; Jin, Ying; Zou, Gang; Tang, Jingfeng; Ge, Zhen; Liu, Yi
Abstract : Background . FGF-2 (basic fibroblast growth factor) has a positive effect on the proliferation and differentiation of many kinds of MSCs. Therefore, it represents an ideal molecule to facilitate tendon-to-bone healing. Nonetheless, no studies have investigated the application of FGF-2-induced human amniotic mesenchymal stem cells (hAMSCs) to accelerate tendon-to-bone healing in vivo. Objective . The purpose of this study was to explore the effect of FGF-2 on chondrogenic differentiation of hAMSCs in vitro and the effect of FGF-2-induced hAMSCs combined with a human acellular amniotic membrane (HAAM) scaffold on tendon-to-bone healing in vivo. Methods . In vitro, hAMSCs were transfected with a lentivirus carrying the FGF-2 gene, and the potential for chondrogenic differentiation of hAMSCs induced by the FGF-2 gene was assessed using immunofluorescence and toluidine blue (TB) staining. HAAM scaffold was prepared, and hematoxylin and eosin (HE) staining and scanning electron microscopy (SEM) were used to observe the microstructure of the HAAM scaffold. hAMSCs transfected with and without FGF-2 were seeded on the HAAM scaffold at a density of 3 × 10 5 cells/well. Immunofluorescence staining of vimentin and phalloidin staining were used to confirm cell adherence and growth on the HAAM scaffold. In vivo, the rabbit extra-articular tendon-to-bone healing model was created using the right hind limb of 40 New Zealand White rabbits. Grafts mimicking tendon-to-bone interface (TBI) injury were created and subjected to treatment with the HAAM scaffold loaded with FGF-2-induced hAMSCs, HAAM scaffold loaded with hAMSCs only, HAAM scaffold, and no special treatment. Macroscopic observation, imageological analysis, histological assessment, and biomechanical analysis were conducted to evaluate tendon-to-bone healing after 3 months. Results . In vitro, cartilage-specific marker staining was positive for the FGF-2 overexpression group. The HAAM scaffold displayed a netted structure and mass extracellular matrix structure. hAMSCs or hAMSCs transfected with FGF-2 survived on the HAAM scaffold and grew well. In vivo, the group treated with HAAM scaffold loaded with FGF-2 -induced hAMSCs had the narrowest bone tunnel after three months as compared with other groups. In addition, macroscopic and histological scores were higher for this group than for the other groups, along with the best mechanical strength. Conclusion . hAMSCs transfected with FGF-2 combined with the HAAM scaffold could accelerate tendon-to-bone healing in a rabbit extra-articular model.